A Note on the Growth of Nonbank Financial Intermediaries and Interest Rate Determination - Ettin, Edward C. (Quarterly Journal of Economics, 1964)
Journal Article A Note on the Growth of Nonbank Financial Intermediaries and Interest Rate Determination Get access Edward C. Ettin Edward C. Ettin Duke University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 78, Issue 4, November 1964, Pages 649–652, https://doi.org/10.2307/1879663 Published: 01 November 1964